The contemporary artist in front of the transformation of his works. The elapse of time and its effect on materiality - Llamas-Pacheco, Rosario (Arte, Individuo y Sociedad, 2016)
The passage of time has an inevitable impact on artworks. In the case of many of the contemporary art aesthetic, cultural or social values present in them, are linked to the appearance and premeditated use of matter. His transformation has an impact on the intent and aesthetic discourse, so that a deep reflection on the concept of authenticity of the artwork or premature ruin is necessary. Moreover, thanks to the figure of the contemporary artist is possible to document the current production to determine if the mutations of matter affect the essential in their works. Thus, the work has achieved specific, in the case of several key Spanish artists, what aspects should, because they are essential, to remain unchanged over the years.